Toledo Adolescent Relationships Study (TARS): Wave 2, 2002 - Giordano, Peggy C. ([Verlag nicht ermittelbar], 2011)
This study explores the relationship qualities and the subjective meanings that motivate adolescent behavior. More specifically, this study seeks to examine the nature and meaning of adolescent relationship experiences (e.g., with family, peers, and dating partners) in an effort to discover how experiences associated with age, gender, race, and ethnicity influence the meaning of dating relationships. The study further investigates the relative impact of dating partners and peers on sexual behavior and contraceptive practices, as well as involvement in other problem behaviors that can contribute independently to sexual risk taking. The longitudinal design of the Toledo Adolescent Relationships Study (TARS) includes a schedule of follow-up interviews occurring one, three, and five years after the initial interview. Three waves of data have been collected (2001, 2002, and 2004) and a fourth wave is scheduled for collection (2006). Data were collected from adolescent respondents through structured in-home interviews utilizing laptop computers. In-depth interviews were conducted at the first wave with a subsample (n=100) of the respondents. Parent data was collected via a short, self-administered questionnaire at the first wave.